KINERJA PERUSAHAAN DAN PENGARUHNYA TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2014-2016 - Janny Rowena; Hendra Hendra (STIE Wiyatamandala, 2018)
This research was conducted to examine the influence of return on asset, return on equity, and Tobin’s Q to dividend policy in manufactured company in Indonesia Stock Exchange for period 2014 - 2016. There are four variables: dividend policy as the dependent variable, while the ROA, ROE, and Tobin’s Q as the independent variables. The analysis technique used in this research is multiple linier regressions. Based on statistical t test, return on asset have significant influenced on dividend policy because the significant value is less than 0,05. Meanwhile, ROE and Tobins Q doesn’t have a significant influence because the significant value is more than 0,05. Based on statistical F test indicates that variables ROA, ROE, and Tobins Q simultantly affect to dividend policy. Result of coefficient determination test showed that ROA, ROE, and Tobins Q explained the firm value 40,9%, and the rest is influenced by other variables outside the model.